The impact of the social sciences how academics and their research make a difference - Bastow, Simon 1972-; Dunleavy, Patrick; Tinkler, Jane (Sage, 2014)
Based on a three year research project studying the impact of academics on business, government and civil society sectors, this groundbreaking book undertakes the most thorough analysis yet of how academic research in the social sciences achieves public policy impacts, contributes to economic prosperity, and informs public understanding of policy issues--Source other than Library of Congress.